Ultrasensitive tau biosensor cells detect no seeding in Alzheimer’s disease CSF - Hitt, Brian D. (Acta Neuropathol Commun, 2021)
Tau protein forms self-replicating assemblies (seeds) that may underlie progression of pathology in Alzheimer’s disease (AD) and related tauopathies. Seeding in recombinant protein preparations and brain homogenates has been quantified with “biosensor” cell lines that express tau with a disease-associated mutation (P301S) fused to complementary fluorescent proteins. Quantification of induced aggregation in cells that score positive by fluorescence resonance energy transfer (FRET) is accomplished by cell imaging or flow cytometry. Several groups have reported seeding activity in antemortem cerebrospinal fluid (CSF) using various methods, but these findings are not yet widely replicated. To address this question, we created two improved FRET-based biosensor cell lines based on tau expression, termed version 2 low (v2L) and version 2 high (v2H). We determined that v2H cells are ~ 100-fold more sensitive to AD-derived tau seeds than our original lines, and coupled with immunoprecipitation reliably detect seeding from samples containing as little as 100 attomoles of recombinant tau fibrils or ~ 32 pg of total protein from AD brain homogenate. We tested antemortem CSF from 11 subjects with a clinical diagnosis of AD, 9 confirmed by validated CSF biomarkers. We used immunoprecipitation coupled with seed detection in v2H cells and detected no tau seeding in any sample. Thus we cannot confirm prior reports of tau seeding activity in the CSF of AD patients. This next generation of ultra-sensitive tau biosensors may nonetheless be useful to the research community to quantify tau pathology as sensitively and specifically as possible. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40478-021-01185-8.